A novel method for the determination of diffusion coefficients in amorphous poly(3-hydroxybutyrate). (October 2017) - Polyák, Péter; Szemerszki, Dóra; Benke, Henrik Christopher; Pukánszky, Béla
Abstract: A novel approach is proposed for the determination of the diffusion coefficient of certain drugs in amorphous poly(hydroxybutyrate) (PHB), which can be a reliable alternative to the conventional permeation based measurements. The method requires the preparation of PHB films with various concentrations of the drug and if the latter absorbs in the visible wavelength range, its concentration gradient in the polymer film as well as the time dependence of the latter can be analyzed quantitatively by following changes in color. Color can be converted into concentration with the help of adequate calibration and thus the dependence of additive concentration on space ( x ) and time ( t ), i.e. the c ( x, t ) function, can be determined relatively easily. The fitting of the numerical solution of Fick's second law onto the measured values provides directly the targeted diffusion coefficient. The comparison of diffusion coefficients obtained by the proposed approach to values published in the literature proved that the new method provides reliable results and requires reasonable time and effort at the same time.